Rainfall Erosivity Spacial Distribuction in Manuel Alves da Natividade River Basin, State of Tocantins, Brazil - Silva Neto, Virgílio Lourenço; Batista, Elismar Dias; Leal Junior, Wilmar Borges; Fabris, Zanine Vargas; Rodrigues, Pedro James Almeida Wolney (Sociedade & Natureza, 2020)
We calculated Manuel Alves da Natividade river basin erosivity, Tocantins state southwest region, using Ordinary kriging interpolator method. All spherical, exponential and Gaussian models were tested. We analyzed Rainfall dates from 1983 to 2013. To map mensal and annual erosivity, we applied geostatistical techniques. Annual erosivity showed values between 8332 and 9253 MJ mm ha-1 h-1 year-1. December presented strongest erosivity numbers, until 2170 MJ mm ha-1 h-1 month-1. No critical erosivity values were found between May and September Northwest, North and Central are critical regions with highest erosivity numbers and demand special attention about soil preservation.